Circular - Schevenels, Walther, b. 1894
011-0070-001 FÉDÉRATION SYNDICALE INTERNATIONALE INTERNATIONAL FEDERATION OF TRADE UNIONS INTERNATIONALER GEWERKSCHAFTSBUND 9, AVENUE D'ORSAY, PARIS-VIIe ADRESSE TELEGRAPHIQUE : TELEGRAPHIC ADDRESS : INTERFED. PARIS TÉLÉPHONE : INVALIDES 45-88 TELEGRAMMADRESSE : Sch/H/sz Situation Espagne 263 9th July, 1937 To Affiliated and Sympathising National Centres Dear Comrades, As you will already have seen from the press and the IFTU's Bulletin, the IFTU General Council decided in Warsaw to intensify the campaign for the unrestricted application of international law to the Spanish democratic Republic, all the consequences of this being fully realised. With this in view, the General Council unanimously decided to organise a special Spanish Propaganda Week simultaneously over the whole world. We should therefore be glad to know if you in your country are prepared and able to arrange such a Spanish Propaganda Week, with the aim of: (1) arousing the public opinion of the whole country to bring pressure to bear on the government, to get the complete restoration to Spain of her rights under international law; and (2) intensifying the relief work, through contributions to the International Solidarity Fund (LSI/IFTU, Paris), reception of evacuated children, women and aged persons, despatch of help in kind, etc. So that adequate preparations can be made, we propose as the date for this Week (it need not, incidentally, be the only one) the 31st July to 6th August. This date is chosen because it coincides with the anniversary of the outbreak of war in 1914. Moreover, we should be able to organise on the 31st July a great demonstration in Paris (meeting of the International Committee of Trade Union Women, demonstration for peace and for Spain with participation of women speakers from different countries and to give the Workers' Olympiad on the 1st August the character of a solidarity demonstration for Spain. We trust that you will be able to use all the means in your power to make this Propaganda Week a great event in your country. Unless there are insurmountable obstacles in the way of holding the Week at this time, we should be very glad if you could agree to the date proposed, as it seems to be the most suitable, in view of the difficulties of finding a date convenient to each of the twenty or twenty-two countries concerned . Yours sincerely, W. Schevenels General Secretary 292/946/11/70